Islam In Malaysia : An Entwined History by Khairudin Aljunied - Sharifah Sophia, Wan Ahmad
Islam in Malaysia is a historical biography befitting the time one finds oneself in. The mainstream discourse of Islam in Malaysia has long been cast in a nationalist paradigm of ethnicity and religion whose selective narrative instructs the ethnic factor as the normative position in approaching Islam. Reminding the contemporary reader that the flourishing of Islam in Malaysia has been forged in a longer duration of time and occupies a wider space than the current nation-state, the author Khairudin Aljunied aims for a broadening of his reader’s perspective. Islam, as per his account, has in fact a cosmopolitan root and such a history deserves an audience among the learned and the hopefuls.